Cultura e negazione. Una nota sul concetto di ‘esperienza’ nella Fenomenologia dello spirito di Hegel (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Moving critically from Giorgio Agamben’s thesis (Infancy and History) about the separation between experience and knowledge and the consequent destruction of experience for contemporary human beings, the essay suggests a reconsideration of Hegel’s notion of Erfahrung. According to the Preface of Hegel’s Phenomenology of Spirit, the very meaning of experience – that is, the chance of developing an authentic “subjectivity” and to eventually achieve the so-called absolute (i.e. “free”) knowing – rather depends on a deeper comprehension of the relationship between individual and collective culture and the dialectical dispositive of negation that already defines our linguistic being in the world. In this sense, the diagnosis of our lack of experience should be at least integrated (if not radically modified) in a Hegelian sense: Poverty of experience depends namely on the inability to think adequately about the processual character of a true Bildung. KEYWORDS: Bildung/culture, experience, negation, subjectivity.